2022
DOI: 10.1101/2022.09.27.509787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the Mechanism of the Proton-Coupled Fluoride Transport in the CLCF Antiporter

Abstract: Fluoride is a natural antibiotic abundantly present in the environment and, in micromolar concentrations, is able to inhibit enzymes necessary for bacteria to survive. However, as is the case with many antibiotics, bacteria have evolved resistance methods, including through the use of recently discovered membrane proteins. One such protein is the CLCF F-/H+ antiporter protein, a member of the CLC superfamily of anion-transport proteins, most notably known for their ability to transport chloride ions. While … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This can be rationalized by fact that the rotation of the E118 side chain is reversible and that the negatively charged carboxylate and fluoride anions can compete with each other for the external binding site. 5 Just like Mills and Torabifard, 22 we found that the unrestrained F cen ions in WT1 diffused quickly away from their initial positions in the binding sites after the simulation started, being 8 Å away within 110 ps for protein monomer A and 690 ps for monomer B, and eventually moved into the bulk solution (Figure S3 in the Supporting Information). In the other models, loosely restrained F cen stayed near the central binding site.…”
Section: Equilibrated MM Modelssupporting
confidence: 73%
See 4 more Smart Citations
“…This can be rationalized by fact that the rotation of the E118 side chain is reversible and that the negatively charged carboxylate and fluoride anions can compete with each other for the external binding site. 5 Just like Mills and Torabifard, 22 we found that the unrestrained F cen ions in WT1 diffused quickly away from their initial positions in the binding sites after the simulation started, being 8 Å away within 110 ps for protein monomer A and 690 ps for monomer B, and eventually moved into the bulk solution (Figure S3 in the Supporting Information). In the other models, loosely restrained F cen stayed near the central binding site.…”
Section: Equilibrated MM Modelssupporting
confidence: 73%
“…(ii) Our simulations followed the original windmill mechanism, where fluoride and E118 side chain compete for the external binding site, whereas the modified windmill mechanism without such competitions was pursued in ref. 22 The repulsions between the negatively charged fluoride and carboxylate of E118 in our simulations will almost certainly lead to a higher barrier. Because two different mechanisms were investigated in this work and in ref, 22 the results in one study do not necessarily rule out the other.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations